Implementation Early of Initiation Breastfeeding (EIB) by Health Workers in the Maternity Room of 'Aisyiyah Ponorogo General Hospital During Covid-19 Pandemic - Dian Meilani Saputra; Byba Melda Suhita; Ratna Wardani; Nurdina (Universitas STRADA Indonesia, 2023)
Background: Early of initiation breastfeeding (EIB) can reduce the Infant Mortality Rate (IMR) and Maternal Mortality Rate (MMR). The COVID-19 pandemic reduced early initiation of breastfeeding activities. As a result of the COVID-19 pandemic, access to essential services such as breastfeeding counseling in hospitals has been disrupted. Purpose: The purpose of this study is that researchers want to examine the implementation of the EIB by health workers in the maternity room of